National Youth Survey (United States): Wave VII, 1987 - Elliott, Delbert S. ([Verlag nicht ermittelbar], 1996)
Youth data for the seventh wave of the National Youth Survey are contained in this collection. This research project, designed to gain a better understanding of both conventional and deviant types of behavior by youths, involved collecting information from a representative sample of young people in the United States. The first wave of this survey was conducted in 1976 (ICPSR 8375), the second in 1977 (ICPSR 8424), the third in 1978 (ICPSR 8506), the fourth in 1979 (ICPSR 8917), the fifth in 1980 (ICPSR 9112), and the sixth in 1983 (ICPSR 9948). For this wave, young adults were interviewed in early 1987 about events and behavior occurring in calendar year 1986, when they were 20 to 29 years of age. Data are available on the demographic and socioeconomic status of respondents, parents and friends, neighborhood problems, education, employment, skills, aspirations, encouragement, normlessness, attitudes toward deviance, exposure to delinquent peers, self-reported depression, delinquency, drug and alcohol use, victimization, pregnancy, abortion, use of mental health and outpatient services, violence by respondent and acquaintances, use of controlled drugs, and sexual activity.